Blockchain-enabled resilience an integrated approach for disaster supply chain and logistics management - Katina, Polinpapilinho F.; Gheorghe, Adrian V. (CRC Press, 2023)
This book provides a first-of-its-kind approach for using blockchain to enhance resilience in disaster supply chain and logistics management, especially when dealing with dynamic communication, relief operations, prioritization, coordination, and distribution of scarce resources -- these are elements of volatility, uncertainty, complexity, and ambiguity (VUCA) describing a dynamic environment that now form the "new norm" for many leaders. Blockchain-Enabled Resilience: An Integrated Approach for Disaster Supply Chain and Logistics Management analyzes the application of blockchain technology used to enable resilience in a disaster supply chain network. It discusses IoT and DVFS algorithms for developing a network-based simulation and presents advancements in disaster supply chain strategies using smart contacts for collaborations. The book covers how success is based on collaboration, coordination, sovereignty, and equality in distributing resources and offers a theoretical analysis that reveals that enhancing resilience can improve collaboration and communication and can result in more time-efficient processing for disaster supply management. The bookoffersa first-of-its-kind approach for managers and policy-makers as well as researchers interested in using blockchain to enhance resilience in disaster supply chains, especially when dealing with dynamic communication, relief operations, prioritization, coordination, and distribution of scarce resources. Practical guidance is provided for managers interested in implementation. A robust research agenda is also provided for those interested in expanding present research.
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on April 07, 2023)
Keywords: Business logistics; Humanitarian assistance -- Management; Blockchains (Databases) -- Industrial applications; Logistique (Organisation); Aide humanitaire; Gestion; Chaînes de blocs; Applications industrielles; TECHNOLOGY / Manufacturing; Business logistics; Data processing; Emergency management; Data processing